2005
DOI: 10.1002/pc.20127
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of pultruded composites containing fillers and low profile additives

Abstract: This article deals with the effect of fillers and additives content on the physical and mechanical properties of unidirectional pultruded glass/polyester composites. The physical characterization consisted of determining the void volume fraction (Vv), density, shrinkage ratio, coefficient of thermal expansion (CTE), and dynamic mechanical properties. The mechanical tests consisted of three-point-bending tests under static, impact, and fatigue loading. The low profile additive (LPA) has been found to compensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Also, the CTE increases first with the LPA content up to 5% and decreases afterward between 5% and 40%. This behavior is in agreement with CTE measurements performed in [34]. This reduction of thermal expansion was attributed to the presence of microvoids in the microstructure due to the LPA shrinkage compensation mechanism.…”
Section: Dimensional Changes Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the CTE increases first with the LPA content up to 5% and decreases afterward between 5% and 40%. This behavior is in agreement with CTE measurements performed in [34]. This reduction of thermal expansion was attributed to the presence of microvoids in the microstructure due to the LPA shrinkage compensation mechanism.…”
Section: Dimensional Changes Analysissupporting
confidence: 91%
“…It was determined that there is an optimal LPA content to compensate for cure shrinkage that varies depending on the resin and LPA systems studied. Boukhili et al [34] also examined the influence of LPA on the thermal expansion. It was observed that the coefficient of thermal expansion (CTE) of a glass/polyester composite increased with an LPA content variation from 0% to 15%, but then decreased afterward at 20% LPA content.…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend was found in the literature for the Young's modulus variation with LPA content [10][11][12][13][14][15] and the flexural strength evolution with an increase in LPA content for pultruded composites. 17 In the case of the 40% LPA content, the flexural modulus and strength standard deviations appeared to be higher. This was attributed to a less homogeneous structure of the matrix due to the development of the LPA rich phase.…”
Section: Flexural and Shear Propertiesmentioning
confidence: 92%
“…17 With the addition of LPA, the apparent short-beam strength decreases. Reductions of 18% and 21% of the apparent short-beam strength were obtained at 10% and 40% LPA contents, respectively.…”
Section: Khoun Et Al 819mentioning
confidence: 97%
“…Generally, additive and fillers are used in the pultrusion process to enhance the physical and mechanical properties of the pultruded profiles, to solve production difficulty and to reduce the production cost (Boukhili et al, 2006). sulfonic acid (Ma et al,1997) Science Publications Figure 9 shows typical load-displacement curves for pultruded glass/polyester composites containing different amounts of fillers and tested at L/h = 24.…”
Section: Mechanical Properties Of Pultruded Compositesmentioning
confidence: 99%